Bushy‐Crested Hornbills Successfully Hunting Flying Bats in Gomantong Caves, Malaysia - José L. Tella; Cristina Fuentes‐Sendín; Carlos Gutiérrez‐Expósito; Gema Ruiz‐Jiménez; Raquel Sainz‐Elipe; Cristina B. Sánchez‐Prieto; David Serrano (Ecology and Evolution)
ABSTRACT Hornbills living in tropical forests are predominantly frugivorous, but some species incorporate small animals into their diets, and bats have only been anecdotally recorded among their prey. However, it is not well known how they are captured and how often. We observed bushy‐crested hornbills (Anorrhinus galeritus) capturing wrinkle‐lipped free‐tailed bats (Mops plicatus) in flight as thousands of them emerged from a large cave‐roost in Bornean Malaysia. At least eight individuals successfully hunted flying bats by perching on dry branches hanging from the main entrance of the cave, using two tactics: (1) by jumping and making short flights until catching the flying bats (i.e., hawking), and (2) perching, waiting for bats that fly by at short distances, catching them with quick movements of the beak (i.e., snatching). This does not appear to be an anecdotal behavior, but rather one that has gone unnoticed until now. The number of hornbills hunting was greater than that of bat hawks (Machaeramphus alcinus), a diurnal raptor specialized in hunting bats. Further systematic monitoring of these and other diurnal avian predators is necessary to fully understand the pressure they exert on bats.